Emotional intelligence and the dark triad: a latent profile analysis to investigate the Jekyll and Hyde of the emotionally intelligent manager - Haag, Christophe; Poirier, Clément; Bellinghausen, Lisa (Frontiers in Psychology, 2024)
Managers sometimes have a bad reputation as they are often perceived as more manipulative than other employees. This study focuses on the Dark Triad (DT)-comprising psychopathy, Machiavellianism, and narcissism-and its connection with managers' "Ability" Emotional Intelligence (AEI). The link between DT (measured through the Dirty Dozen) and managers' AEI (measured through QEPro, an AEI performance test) was examined through a Latent Profile Analysis (LPA). We identified two AEI latent profiles within a heterogeneous population of 231 French managers. Our results show that managers with the FEP (Full Emotional Processing) profile are less Machiavellian (relative to the MEP -Minimal Emotion Processing-profile). Our results show that identifying AEI profiles may be a practical way to prevent toxic Management.